2014
DOI: 10.1159/000358718
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of miR-3928 Promoted Osteosarcoma Growth

Abstract: Background: Osteosarcoma is the most common primary bone malignancy in children and young adults. Most failures of osteosarcoma treatment were due to resistance to chemotherapy. Development of new therapy required elucidation underlying molecular mechanism. Many miRNAs have been proved to be involved in the pathogenesis of osteosarcoma. Methods: MiR-3928 expression level was assayed by qRT-PCR. MiRNA mimics or ASO were transfected for up-regulation or down-regulation of miR-3928 expression. Cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Discussion miR-574 has been found to be upregulated in several types of cancers, including lung cancer, bladder cancer and prostate cancer (11)(12)(13)19). Foss et al (17) also suggested miR-574 as a serum biomarker of non-small cell lung cancer.…”
Section: Downregulation Of Mir-574-3p Inhibited Cell Growth and Inducmentioning
confidence: 94%
See 2 more Smart Citations
“…Discussion miR-574 has been found to be upregulated in several types of cancers, including lung cancer, bladder cancer and prostate cancer (11)(12)(13)19). Foss et al (17) also suggested miR-574 as a serum biomarker of non-small cell lung cancer.…”
Section: Downregulation Of Mir-574-3p Inhibited Cell Growth and Inducmentioning
confidence: 94%
“…All diagnoses were based on pathological and/or cytological evidence (10). The histological features of the specimens were evaluated by senior pathologists according to the World Health Organization classification criteria (11)(12)(13). Tissues were obtained prior to chemotherapy and radiotherapy, and were immediately frozen and stored at -80˚C prior to reverse-transcription quantitative polymerase chain reaction (RT-qPCR) assay (3,5,10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FACS analysis was performed as previously described [25]. Cell apoptosis was determined using an annexin V-FITC apoptosis detection kit (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Ankur et al showed that up-regulation of miR-100 inhibited mTOR signaling and enhanced sensitivity to RAD001 [58]. Interestingly, Huang and his colleagues identified for the first time that miR-100 might act as a tumor suppressor in the progression of osteosarcoma by controlling the direct target gene Cyr61 [75,99]. It has been reported that Cyr61 promotes cell proliferation and inhibit cell apoptosis by binding to different types of integrin molecules, which resulted in down-regulating p53 expression and up-regulating NF-κB expression through PI3K/Akt/ mTOR pathways [100,101].…”
Section: Mir-100 In Cancer Proliferation and Apoptosismentioning
confidence: 99%